Analisis Program One Agency One Innovation Dalam Meningkatkan Pelayanan Publik di Kabupaten Wajo - Herdi Syam; Eka Patmasari; Andi Anugrah (Department of Public Administration, Muhammadiyah University of Makassar, 2021)
Encouraging innovation in government agencies is one of the ways to meet the demands of society for quality public services, the implementation of the One Agency One Innovation program as an effort to accommodate the creative and innovative ideas of the state civil servants in Indonesia which are welcomed by local government by holding the same program at the regional level and then the winner will represent at the national level.This research was conducted to analyze the One Agency One Innovation program in Wajo Regency which aims to find out how this program can motivate innovators to improve the quality of public services through their ideas. The method used is qualitative by collecting data using literature review, observation and interviews. The results of this study indicate that the motivation of the innovators is caused by the desire for achievement, the motivation of the leader, the desire to solve problems and the implementation of science. In terms of public services, innovators are able to carry the theme of innovation based on the scope of public services based on Law Number 25 of 2009 concerning public services, including; education, teaching, employment and business, information and communication, health and social security. The theme of innovation being proposed is a sector that is currently the main focus of the government. Keywords: agency, innovation, public service